Вплив препарату Нематофагін на показники білкового обміну та ферментну активність крові кролів за пасалурозу - Дуда, Юлія Вікторівна; Duda, Yuliya; Прус, М. П.; Prus, M. P.; Кунєва, Лариса Володимирівна; Kuneva, Larisa (Житомирський національний агроекологічний університет, 2017)
Protein metabolism and blood enzymes coordinate, regulate and integrate most of the chemical transformations in the body. Any deviation from the normal physiological state of the organism is reflected in protein metabolism and enzyme activity. Therefore, knowledge of the patterns of these changes in a specific pathological process is important for understanding the mechanisms of the disease and the choice of tactics of therapeutic measures. As an anthelmintic, we used the Nematofagin biopreparation based on the fungus Arthrobotris oligospora. The fungus catches and neutralizes nematodes in the process of growth. The action of the preparation Nematophagin reduced the intensity of the invasion by 3.36 times. The parameters of protein metabolism and enzymatic activity of blood make it possible to characterize the functional state of internal organs. In the blood of rabbits, the content of total protein decreased by 8.98% (p <0.05), globulins by 1.24 times (p <0.05) due to all fractions, including β- and γ-globulins decreased by 1.78 times (p <0.05) and 1.26 times (p <0.05), respectively, as well as the urea content by 15.63% (p <0.05) as compared to the control under the action of the biological preparation. Under the action of Nematophagin, uric acid in serum increased by 1.39 times (p <0.05). The activity of enzymes in the blood of experimental rabbits underlines the positive effect of the drug on functional capacity, both liver and pancreas and kidneys. Thus, the activity of ALT, α-amylase and (p <0.01) of gamma-glutamintranspeptidase decreased significantly (p <0.001). At the same time, the decrease in the activity of the enzyme cholinesterase (p <0.05) was observed only in the control. Білковий обмін і ферменти крові координують, регулюють та інтегрують більшість хімічних перетворень в організмі. Будь-які відхилення від нормального фізіологічного стану організму відбиваються на білковому обміні та активності ферментів. Тому знання закономірностей цих змін при конкретному патологічному процесі має важливе значення для розуміння механізмів хвороби і вибору тактики терапевтичних заходів. В якості антгельмінтика нами був застосований біопрепарат Нематофагін на основі гриба Arthrobotris оligospora. Гриб в процесі росту уловлює та нейтралізує нематоди. За дії біопрепарату Нематофагін інтенсивності інвазії зменшилась в 3,36 рази. Показники білкового обміну та ферментна активність крові дають можливість охарактеризувати функціональний стан внутрішніх органів. У крові кролів під впливом біопрепарату знизився вміст загального білку на 8,98% (p<0,05), глобулінів в 1,24 рази (p<0,05) за рахунок всіх фракцій, зокрема вірогідно зменшились β- та γ-глобуліни в 1,78 рази (p<0,05) та в 1,26 рази (p<0,05) відповідно, а також вміст сечовини на 15.63% (p<0,05) порівняно з контролем. Нематофагін сприяв підвищенню в 1,39 рази (p<0,05) сечової кислоти в сироватці крові. Активність ферментів крові дослідних кролів підкреслює позитивний вплив препарату на функціональну здатність печінки, підшлункової залози та нирок. Так, вірогідно (p<0,001) зменшились активності АлАТ, α-амілази та (p<0,01) гама-глутамінтранспептидази. При цьому зниження активності ферменту холінестерази (p<0,05) спостерігали тільки у контролі.
The effect of Nematophagin on protein metabolism and enzymatic activity of blood of rabbits with pasalurosis
Keywords: пасалуроз; pasalurosis; нематофагін; nematophagin; білковий обмін; protein metabolism; ферменти; enzymes; Passalurus ambiguus; Passalurus ambiguus; альбуміни; albumins; глобуліни; globulins; нематодози кролів; rabbit nematodes